(untitled) (Research, Society and Development, 2024)
This literature review aims to analyze the influence of the impact of lifestyle habits on the increased risk of degenerative disorders, addressing aspects related to aging, dementia and the role of the intestinal microbiota, the influence of diet on these processes. Population aging has been a reality in Brazil, with a significant increase in the elderly population in recent decades. Dementias, such as Alzheimer’s disease, represent a global challenge due to their social and economic impact, studies indicate an association between the intestinal microbiota and the development of these neurodegenerative diseases. Diet plays a crucial role in the prevention and management of dementia, with evidence suggesting that certain nutrients, such as vitamins D, E, omega-3 fatty acids and antioxidants, can positively influence cognitive function and slow the progression of the disease. However, many older adults face challenges in obtaining adequate nutrition due to a variety of factors, including dental problems, low income, and depression. Furthermore, supplements such as polyunsaturated fatty acids, vitamin D, Coenzyme Q10 and creatine have been investigated for their potential neuroprotective effect and ability to reduce oxidative stress, improve cognitive function and slow the progression of neurodegenerative diseases. However, more research is needed to determine the exact role of these supplements and establish proper usage protocols. In summary, the review highlights the importance of adequate nutrition in promoting brain health and managing dementia, highlighting the need for dietary interventions and supplementation to address the challenges associated with population aging and neurodegenerative diseases.